Penerapan Model Problem Based Learning Berbantuan Media Geogebra Untuk Meningkatkan Kemampuan Berpikir Kreatif Matematis Siswa di MTs Citra Abdi Negoro - Yuki Indayanti; Prihatin Ningsih Sagala (Journal of Student Research, 2023)
This study aims to find out how to improve students' mathematical creative thinking skills after using the Problem Based Learning model assisted by Geogebra media and to find out how students' answers process in solving problems on the mathematical creative thinking ability test after applying the Problem Based Learning model assisted by Geogebra media. This type of research is Classroom Action Research (PTK) which was conducted in two cycles, the subjects in the study were class IX-3 MTs Citra Abdi Negoro, totaling 27 students. This research is said to be successful if it meets the indicators of success, namely, (1) The level of students' mathematical creative thinking ability increases with a value of ≥ 85% at least in the medium category, (2) The process of completing student answers with a value of ≥60% at least in the good category, (3) The results student and teacher observations show a good category. Based on the results of the study, the average initial ability test score of 58.10 increased to 61.34 in cycle I and 80.55 in cycle II. There was also an increase in classical completeness, in the creative thinking ability test of 8 students (29.63%) in the initial ability test increased to 12 students (44.44%) in cycle I and 25 students (92.59%) in cycle II. For the process of student answers from cycle I with an average presentation of 50 students' answer processes, 31% increased to 70.67% in cycle II. Based on the results of the study it can be concluded that the Problem Based Learning model assisted by Geogebra media can improve students' creative thinking skills.